Population and Microhabitat of Uca spp. in Mangrove Conservation Area of Pantai Panjang, Bengkulu - Hasan, Rusdi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Fiddler crabs (Uca spp.) are distributed widely in tropical and subtropical areas in the world. They live in the sandy and muddy bay habitats of intertidal zone. This study aimed to find species abundance, microhabitat and population density of fiddler crabs in mangrove conservation area of Pantai Panjang, Bengkulu.  The sampling was conducted for three months started from December 2013 to February 2014. Sampling locations were decided purposively on the area consist of four microhabitats, i.e. sandy, muddy, muddy around decay plant roots and around mangrove roots. Samples of Uca were collected from 1x1 m of sixty quadrants.   The results found seven species of fiddler crabs i.e. U. perplexa, U. lactea, U. jocelynae, U. forcipata, U. triangularis, U. rosea, and U. dussumieri. They were distributed at four microhabitats. The microhabitats of U. perplexa, U. lactea, U. jocelynae, U. forcipata, U. triangularis, U. rosea, and U. dussumieri were around mangrove roots and sandy, around mangrove roots, muddy, muddy, muddy around decay plants, muddy and sandy areas, respectively. Among those species, U. perplexa was the most abundant population whereas U. dussumieri was the less one. Popolation density of fiddler crabs were U. perplexa  5.48  ind/m2, U. lactea 4.25 ind/m2, U. jocelynae , 1.47 ind/m2, U. forcipata 0.28 ind/m2,  U.triangularis 0.18 ind/m2,  U. rosea 2.17 ind/m2 and U. dussumieri 0.12 ind/m2.Key words: Mangrove, microhabitat, population, Uca spp.